Penerapan Sistem Pendukung Keputusan Perekrutan Dosen Baru Pada Poltek AMI Medan Menggunakan Metode Simple Additive Weighting (SAW) - Yuliannisa Yuliannisa (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
This study examines the recruitment of new lecturers at Poltek Ami Medan. At Poltek Ami Medan, it takes a long time to rank and analyze for the recruitment of new lecturers. Recruitment of new lecturers aims to find new lecturers who are qualified and in accordance with the required criteria so that decision making becomes more effective and efficient. The calculation of the recruitment of new lecturers uses the Simple Additive Weighting (SAW) method. This method performs a search for the weighted sum of the performances that are ranked on the alternatives in all their attributes. The categories used for this calculation are 3 (three) categories, namely the category of educational qualifications, microteaching tests, and interview tests. The results of this study were carried out by assessing by weight using the SAW method, then 3 (three) applicants with the highest score were obtained, namely applicant 1 = 37.5, and applicant 9 = 10 with the lowest score. Judging from the processing results, applicant 1 has the highest score of 37.5 stating that applicant 1 is recommended to be a new lecturer at Poltek Ami Medan. The results of the assessment of determining the acceptance of new lecturers are seen from the highest ranking with the largest ranking value, namely the 1st applicant.